Implementasi Aplikasi Sistem Pakar Untuk Mendiagnosa Penyakit Insomnia Menggunakan Metode Backward Chaining - alwendi; Mandopa, andi saputra (Gayaku Publisher, 2024)
Health is the most important thing for everyone. Without a strong and healthy body, a person will have difficulty carrying out activities. Due to limited information about children's illnesses, it is difficult for parents to predict what disease their child will suffer from. This is something new for new parents. Parents want to hand over the diagnosis of the disease to a health professional or doctor. Insomnia is a sleep disorder that attacks people who feel tired or lethargic throughout the day, have difficulty falling asleep continuously, or wake up in the middle of the night and cannot go back to sleep. The causes include psychological factors, physical factors, environmental factors, and lifestyle habits. For some people, the cost of consulting a specialist or expert is not cheap. Therefore, many parents choose to raise their children themselves. Because treatment of the disease is delayed, the disease becomes more severe and difficult to cure. Lack of parental knowledge about the symptoms of diseases that occur in children. The role of pediatricians in treating children's illnesses is very important, but is often hampered by the limited number of pediatricians and the large number of people who need treatment at the same time. To reduce these limitations, it is necessary to create a tool in the form of an expert system. According to the capabilities of an expert system, it is a branch of artificial intelligence, namely it can act like an expert in a certain field of science.